Direct photoresponsive inhibition of a p53-like transcription activation domain in PIF3 by Arabidopsis phytochrome B - Chan Yul Yoo (Nature Portfolio, 2021)
Photoactivated phytochrome B regulates gene expression by interacting with PIF transcription factors. Here the authors show that PIF3 contains a p53-like transcription activation domain (AD) and that PHYB can directly suppress PIF3 transactivation activity by binding adjacent to the AD.